2006
DOI: 10.1080/16066350600691683
|View full text |Cite
|
Sign up to set email alerts
|

Constructing maturity through alcohol experience–Focus group interviews with teenagers

Abstract: Danish 14-and 15-year-olds are at the top of the European list when it comes to drinking and drunkenness. The aim of this article is to demonstrate how the struggle for social recognition -with alcohol as the central marker -transpires in groups of teenagers in Denmark. This article shows how alcohol experience and positive attitudes towards drinking are related to popularity and influence in the peer group. The function of alcohol in teenagers' struggle for recognition is so strong that the participants who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 4 publications
3
58
0
2
Order By: Relevance
“…Therefore, micro interactive sociological concepts of social settings (drinking situations) are often applied to this type of research (Demant and Järvinen, 2006;Douglas, 2003;Gusfield, 2003;Maunu, 2007a, 2007b). Some studies examine in-depth specific drinking locations such as pubs (for example, Hunt and Satterlee, 1986;Leyshon, 2008), house parties (for example, Järvinen and Østergaard, 2009;Demant and Østergaard, 2007) and tourist locations (for example, Tutenges, 2011).…”
Section: Urban Drinking Spacesmentioning
confidence: 99%
“…Therefore, micro interactive sociological concepts of social settings (drinking situations) are often applied to this type of research (Demant and Järvinen, 2006;Douglas, 2003;Gusfield, 2003;Maunu, 2007a, 2007b). Some studies examine in-depth specific drinking locations such as pubs (for example, Hunt and Satterlee, 1986;Leyshon, 2008), house parties (for example, Järvinen and Østergaard, 2009;Demant and Østergaard, 2007) and tourist locations (for example, Tutenges, 2011).…”
Section: Urban Drinking Spacesmentioning
confidence: 99%
“…Focus groups were used to allow participants to draw on their personal experience and knowledge of their immediate social groups (Backett-Milburn, Cunningham-Burley and Davis 2003). The focus groups facilitated social interaction and debate amongst peer groups about drinking practices (Demant and Jarvinen 2006). The decision to use focus groups was made in consultation with the funders and Liverpool Healthy School Team.…”
mentioning
confidence: 99%
“…Had Chikere and his colleague conducted interviews or focus groups, may be they would have uncovered reason(s) for this social change which arguably is due to the influence of globalization because studies conducted in Denmark reported that young people used drunkenness as a resource for constructing social identity, but this finding was only possible due to the application of qualitative methods (Demant and Järvinen 2006). Because qualitative methods such as interviews help to capture how people ''actively construct their social world'', Chikere and colleague would have been better positioned to elicit richer and insightful data on the participants' experiences with alcohol by asking questions on why and how these students use alcohol consumption as a password to the world of fame on campus (Silverman 2011, p.169) despite the fact that young people are culturally supposed to be teetotallers in the part of Nigeria they studied.…”
Section: Discussion and Conclusion The Necessities Of Mixed Methods Dmentioning
confidence: 97%